The molecular species responsible for α1‐antitrypsin deficiency are suppressed by a small molecule chaperone. (11th November 2020) - Ronzoni, Riccardo; Heyer‐Chauhan, Nina; Fra, Annamaria; Pearce, Andrew C.; Rüdiger, Martin; Miranda, Elena; Irving, James A.; Lomas, David A.
Abstract : The formation of ordered Z (Glu342Lys) α1 ‐antitrypsin polymers in hepatocytes is central to liver disease in α1 ‐antitrypsin deficiency. In vitro experiments have identified an intermediate conformational state (M*) that precedes polymer formation, but this has yet to be identified in vivo . Moreover, the mechanism of polymer formation and their fate in cells have been incompletely characterised. We have used cell models of disease in conjunction with conformation‐selective monoclonal antibodies and a small molecule inhibitor of polymerisation to define the dynamics of polymer formation, accumulation and secretion. Pulse‐chase experiments demonstrate that Z α1 ‐antitrypsin accumulates as short‐chain polymers that partition with soluble cellular components and are partially secreted by cells. These precede the formation of larger, insoluble polymers with a longer half‐life (10.9 ± 1.7 h and 20.9 ± 7.4 h for soluble and insoluble polymers, respectively). The M* intermediate (or a by‐product thereof) was identified in the cells by a conformation‐specific monoclonal antibody. This was completely abrogated by treatment with the small molecule, which also blocked the formation of intracellular polymers. These data allow us to conclude that the M* conformation is central to polymerisation of Z α1 ‐antitrypsin in vivo ; preventing its accumulation represents a tractable approach for pharmacological treatment of this condition; polymers are partially secreted; and polymers exist as two distinct populations in cells whose different dynamics have likely consequences for the aetiology of the disease. Abstract : The formation of ordered Z α1 ‐antitrypsin polymers is central to liver disease in α1 ‐antitrypsin deficiency. The nascent α1 ‐antitrypsin folds via the M* intermediate to native monomer or becomes incorporated into a soluble polymer that can be secreted, degraded or precipitate as insoluble inclusions. We describe the kinetics of the clearance of Z α1 ‐antitrypsin polymers and show that they can be abolished with a small molecule preventing the formation of M*.